2013
DOI: 10.5367/ihe.2013.0173
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education and Economic Development in Nigeria: Policy Issues and Options

Abstract: The standard of education in Nigeria has been declining, the level of unemployment continues to rise and the nation's economic development is stagnant. Its educational institutions appear to engage more in unproductive paperwork and teaching than in entrepreneurship education that would help to equip young graduates to become self-employed and employers. In 2011 some 24% of Nigerians were jobless, with unemployment rates of over 17% in urban areas and nearly 26% in rural areas. A productive education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…At the macro level, Udefuna et al (2013) expound inadequate capacity and the perennial policy failures of the Ministry of Education, the Tertiary Education Fund and the National Universities Commission as converging issues impeding the effectiveness of EE programmes in Nigeria. On the current state of research, in their systematic review of 213 articles on EE in Nigeria, Lemun et al (2018) observe that studies are more inclined to track entrepreneurial awareness and, consequently, overlook students' entrepreneurial intention.…”
Section: Context Of the Studymentioning
confidence: 99%
“…At the macro level, Udefuna et al (2013) expound inadequate capacity and the perennial policy failures of the Ministry of Education, the Tertiary Education Fund and the National Universities Commission as converging issues impeding the effectiveness of EE programmes in Nigeria. On the current state of research, in their systematic review of 213 articles on EE in Nigeria, Lemun et al (2018) observe that studies are more inclined to track entrepreneurial awareness and, consequently, overlook students' entrepreneurial intention.…”
Section: Context Of the Studymentioning
confidence: 99%
“…This may be as a result of the poor or inadequate state of incubation resources provided to students of entrepreneurship which has failed to generate the needed benefits necessary to influence the employment status choice. Ayatse (2013) and Udefuna et al (2013) identified a theory-driven approach, lack of adequate systems to develop curricula and funding challenges as the reasons for the poor state of incubation resources in HEIs. Perhaps this explains why more than 80 per cent of the students reported that the EEP concentrates narrowly on the theoretical rather than the practical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, the experience with formal education dates back to as early as 1925. The first colonial policy on education targeted vocational education (Ajayi, 1975), which went through different phases from the 1930s and early 1950s until a formal policy on education, the Nigeria National Policy on Education was launched in 1981 to link education to industrialization through a focus on small firms (Wennekers and Thurik, 1999;Aladekomo, 2004;Udefuna et al, 2013) birthing the concept of entrepreneurial education. However, it was in 2007 that entrepreneurship education was fully embraced in higher educational institutions (Dakung et al, 2017) to promote entrepreneurship (Yatu, Bell and Loon, 2018) focussed on developing the outcome-based aspects of the HCT.…”
Section: Entrepreneurship Education Programme and Attitude Towards Self-employmentmentioning
confidence: 99%
“…Considerable research has been undertaken in entrepreneurship education from various perspectives (e.g., government/policy, education, and training) (Udefuna et al, 2013). Research has nonetheless indicated that the individual plays a primary role in the entrepreneurial process, i.e.…”
Section: Discussion and Research Gapsmentioning
confidence: 99%
“…shows a drop in the percentage of the research conducted between 2012 and 2013, perhaps due to the cooling effect of the government policy intervention on entrepreneurship education(Udefuna et al, 2013). The percentage of the research contribution, however still increased above what was obtainable in the period before the policy intervention.…”
mentioning
confidence: 93%